Analysis of Cellular Traffic Homogeneity in A Specific Area using Statistical Test - Surahmat, Indar (Semesta Teknika, 2016)
Capacity and coverage are the most important issues on providing services by cellular operator companies. The companies measure the condition of their network and services continuously including data collection, monitoring, evaluation and future prediction.Â These are part of activities to maintain grade of service. In this paper, homogeneity analysis in cellular traffic data is analysed. This step is a part of evaluation of current situation which it will be used for planning purposes. It is done by processing data provided by network statistic monitoring tool. This paper limits on analysis in a particular area. The area is served by some cell surrounding the area.Â The result shows a good homogeneity amongst the cell covered a certain area during low traffic (1 am to 1 pm). Otherwise, in high traffic, the serving cells are relatively different in terms of traffic variation and homogeneity test using Fligner-Killeen is more suitable